The dissemination of information relating to the reliability of aircraft and their equipment - Fielding, J. P. (Cranfield University, 1979)
This thesis describes the investigations that have been carried out to examine the feedback of safety and reliability information from civil transport aircraft in the United Kingdom . Many organisations were visited during the course of the study , including several civil transport aircraft operators, airframe and component manufacturer?, and airworthiness authorities . These visits showed the way in which individuals and companies contribute to the information system. The quality of the feedback produced by the information system was assessed by means of a selective survey of development, reliability, and design engineers, etc . who had previously been interviewed during visits to industry . The response of the information system was also gauged by determining the average times required for rectification action to be taken. Parallel studies were conducted, in a limited fashion , to see how the safety and reliability information system of the United States of America ' s civil air transport industry and that of the Royal Air Force, and its suppliers, compared with the British civil air transport industry ' s system . A series of case studies was also performed to investigate , in some detail , what happened to faulty components that were removed from aircraft . The transmission of information from these components to everyone else in the information system , and the rectification action taken , were examined . These studies confirmed that the procedures determined in the previous investigations were, in general , carried out and also highlighted some problems. All of the above investigations showed that the reliability information system was not always adequate, and that a considerable amount of work may have had to be done m achieve adequate reliability control . There were some areas where there was insufficient information for reliability control, and improvements were necessary. The most important recommendation was that a more detailed investigation should be carried out into the feasability of a National Aerospace Reliability Data Bank . A further suggestion was that the Maintenance Review Board consultation system, and its associated reliability and maintainability analyses, should be encouraged . Some work was done to produce design aids such as reliability prediction formulae , etc . These should go some way towards overcoming the problem of design experience retention.